Image-Guided Fine-Needle Aspiration of Secondary Pancreatic Neoplasms: A Case Series and Review of the Literature. Issue 4 (July 2015) - Foo, Wen-Chi; Youens, Kenneth E.; Jowell, Paul S.; Bean, Sarah Muntzing
Abstract : Background: Endoscopic ultrasound–guided fine-needle aspiration (FNA) has become a well-established diagnostic method for evaluation of focal lesions in the pancreas. While the majority of malignant lesions evaluated are primary pancreatic adenocarcinomas, rarely, metastatic lesions to the pancreas are discovered, altering treatment and prognosis for patients. In this retrospective case series study, we describe the 22-year experience with cytologic diagnosis of secondary pancreatic neoplasms in a tertiary medical center. Methods: A search of the electronic pathology database at Duke University Medical Center was performed to identify all patients who had image-guided FNA biopsy of the pancreas diagnosed with secondary neoplasms from 1990 to 2012. Clinical information including sex, age, prior history of malignancy, imaging features of pancreatic mass(es), cytology diagnosis, treatment, and survival was collected. Descriptive statistics were performed. Results: Fifty-three patients had a secondary malignancy of the pancreas from 11 primary sites diagnosed on FNA. The most common primary site was hematopoietic (36%), followed by renal (19%), melanocytic (11%), pulmonary (11%), ovarian (6%), breast (4%), esophageal (4%), and soft tissue (4%). Colorectal (2%), prostatic (2%), and nasopharyngeal (2%) metastases were also identified. No specific imaging features reliably differentiated secondary lesions from primary lesions. The majority of patients (75%) had a prior history of malignancy. Of those without a prior history of malignancy, greater than 90% had a secondary malignancy of hematopoietic origin. Conclusions: Cytologic diagnosis of secondary pancreatic neoplasms is rare. The most common secondary neoplasm of the pancreas was of hematopoietic origin. Imaging characteristics of secondary neoplasms are variable and nonspecific.